2012
DOI: 10.1111/1748-8583.12006
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Trust and HRM: Current insights and future directions

Abstract: Over the last 20 years, HRM has been identified as one of the most influential organisational contexts in which to explore trust, and yet scholars have been slow to look systematically at both the systems and practices that underlie this assertion. Organisations make choices regarding both the design and implementation of HRM policies and practices, with research considering the impact on trust for both key single policy areas and bundles of policies. We outline the previous dominance on teleological approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
(65 reference statements)
0
35
0
Order By: Relevance
“…For example, prior research on HRM and trust has indicated that particular HR practices, such as reward or training policies, might affect trust ( cf. Searle and Dietz, ). Our findings expand on such studies in two ways, namely; (a) by indicating that an underlying reason for prior findings might be because some asymmetries or ‘vulnerabilities’ existed within the studied organisation, even though prior studies did not explicitly investigate this ( cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, prior research on HRM and trust has indicated that particular HR practices, such as reward or training policies, might affect trust ( cf. Searle and Dietz, ). Our findings expand on such studies in two ways, namely; (a) by indicating that an underlying reason for prior findings might be because some asymmetries or ‘vulnerabilities’ existed within the studied organisation, even though prior studies did not explicitly investigate this ( cf.…”
Section: Discussionmentioning
confidence: 99%
“…Scientifically, our investigation also contributes to research on asymmetries in task dependence by (a) supporting (or refuting) current theorising by bringing the investigation to a new level of analysis, namely, the organisational level, (b) expanding current knowledge by investigating a new theoretical mechanism, namely, the mediating effect of trust climate and (c) assessing for the first time whether these asymmetries can be managed by certain HR practices. By doing so, we respond to recent calls in the HRM literature for more cross‐disciplinary work and for better connections between the HRM and the OB literatures (Huselid and Becker, ), in particular regarding HRM and trust (Searle and Dietz, ). As Figure shows, our theory and analyses are at the organisational level; some variables were directly measured at the organisational level, while others were aggregated.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Job satisfaction is recognised as a key mediator between HR practice and positive organisational outcomes (Macky & Boxall, 2007) but is the subject of limited Chinese research (Mao et al, 2013;Zhang et al, 2013). Trust is also emerging as an important employee attitude and has been the subject of much recent Western research (for example, Searle & Dietz, 2012). While Kim et al (2010) argue for its importance, research is again limited in the Chinese context (Zhang et al, 2013).…”
Section: Employee Attitudesmentioning
confidence: 99%
“…We explore trust at the organisational level, reflecting employee perceptions of systems and processes (Searle & Dietz, 2012), here HR practices. Trust has been demonstrated to be important in HPWS in effecting performance improvements (Macky & Boxall, 2007) and in reducing turnover intentions (Wong et al, 2010).…”
Section: Employee Attitudesmentioning
confidence: 99%